Modeling of AP1000 and simulation of 10-inch cold leg small break LOCA using the CESAR thermal-hydraulic module of ASTEC. (August 2015) - Di Giuli, M.; Sumini, M.; De Rosa, F.
Abstract: The Westinghouse AP1000 main characteristic that distinguish it with respects to the modern PWRs is the adoption of several Passive Core Cooling Systems (PCCS) to recover the normal operation or to mitigate the consequences in case of accident. In this paper, modeling and nodalisation of the Reactor Coolant System (RCS), the secondary circuit and all the PCCS for the AP1000 reactor have been studied and a 10-in. small break LOCA scenario has been analyzed using CESAR, the thermal-hydraulic module of the ASTEC V2r2 integral code. The simulation results were compared with those coming from the Westinghouse-developed NOTRUMP code used as reference, showing a reasonable agreement. In case of a 10 inches small break LOCA, the results indicate that the PCCS ensure that the fuel and cladding temperature and the other thermal-hydraulic parameters respect the safety criteria and the safety systems perform their design role during the transient, leading the plant to cold shutdown conditions. Highlights: A Modeling of the AP1000 reactor has been developed using CESAR and ICARE modules of the ASTEC code. A LOCA scenario was analyzed and the results were compared with those obtained by NOTRUMP code. The CESAR modeling of the liquid entrainment and liquid stratification could be improved. The results comparison presented in this study show a reasonable agreement.